ANALISIS HARGA POKOK PRODUKSI DENGAN PENDEKATAN ACTIVITY BASED COSTING PADA PRODUK KEYCHAIN DAN MANGKUK KERAMIK - Caswito, Ade; Suardi, Arief; Ardika, Yanwar Surya; Muslihah, Diah Nita; Anggraini, Novia (Forum Bisnis Kewirausahaan, 2024)
Cost determination is pivotal for business sustainability. This study analyzes the Cost of Goods Manufactured for keychains and ceramic bowls using conventional and Activity-Based Costing (ABC) methods. The difference in overhead costs calculation between these methods is examined. Results indicate lower costs with ABC, specifically Rp 30,807 for keychains and Rp 22,067 for ceramic bowls. This research provides insights for businesses aiming to enhance financial sustainability through efficient cost management.